Protection against N. gonorrhoeae induced by OMV-based meningococcal vaccines are associated with cross-species directed humoral and cellular immune responses - Zhu, Weiyan; Waltmann, Andreea; Little, Marguerite B.; Connolly, Kristie L.; Matthias, Kathryn A.; Thomas, Keena S.; Gray, Mary C.; Sikora, Aleksandra E.; Criss, Alison K.; Bash, Margaret C.; Macintyre, Andrew N.; Jerse, Ann E.; et al. (Frontiers in Immunology, 2025)
IntroductionLimited protective immunologic responses to natural N. gonorrhoeae infection and a lack of knowledge about mechanisms of protection have hampered development of an effective vaccine. Recent studies in humans and mice have found meningococcal outer membrane vesicle-containing vaccines (OMV) induce cross species immune responses against gonococci and are associated with protection. The exact mechanisms or how humoral and cellular immunity are related to protection, remain unclear.MethodsTo study this, we immunized mice with two meningococcal OMV-containing vaccines known to accelerate clearance of N. gonorrhoeae, 4CMenB and OMV from an engineered N. meningitidis strain lacking major surface antigens PorA, PorB, and Rmp (MC58 ΔABR). We assessed serologic and cellular immune signatures associated with these immunizations and assessed bacterial clearance in the mice using a vaginal/cervical gonococcal infection model.ResultsMice immunized with 4CMenB or MC58 ΔABR demonstrated shortened courses of recovery of vaginal N. gonorrhoeae compared to control mice immunized with alum alone. Vaccination with 4CMenB or MC58ΔABR OMV elicited serum and vaginal cross-reactive anti-Ng-OMV antibody responses that were augmented after vaginal challenge with N. gonorrhoeae. Further, splenocytes in 4CMenB and MC58 ΔABR immunized mice exhibited elevated cytokine production after restimulation with heterologous N. gonorrhoeae OMV when compared to splenocytes from Alum immunized mice. We further tested for correlations between bacterial burden and the measured anti-gonococcal immune responses within each vaccination group and found different immunologic parameters associated with reduced bacterial burden for each vaccine.DiscussionOur findings suggest the cross-protection against gonococcal infection induced by different meningococcal OMV vaccines is likely multifactorial and mediated by different humoral and cellular immune responses induced by these two vaccines.